Preparation of Crude Subcellular Fractions by Differential Centrifugation - John Graham (The Scientific World Journal)
The employment of differential centrifugation to prepare crude fractions of subcellular particles from homogenates is often a necessary first step to a subsequent purification of one or more particles on a density gradient. Buoyant density gradient purification of peroxisomes or lysosomes for example is almost invariably carried out on a light mitochondrial fraction so as to eliminate smaller particles that may have similar densities. Unless they are first removed, large rapidly sedimenting particles in homogenates may also disturb shallow gradients designed to fractionate small low-density microsomes.